2005
DOI: 10.1177/1368430205051066
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Intergroup Bias: The Moderating Role of Ingroup Identification

Abstract: Recent work developing interventions designed to reduce intergroup bias has sometimes yielded disparate findings. We tested whether the varying effectiveness of such interventions may have a motivational basis. In two experiments we examined whether differential ingroup identification moderated the effectiveness of a differentiation-reducing intervention strategy. In Experiment 1, thinking of characteristics shared between the ingroup and outgroup reduced ingroup favoritism to a greater extent for lower identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 47 publications
8
51
0
6
Order By: Relevance
“…Categorization models of bias-reduction are linked by the general notion that they reduce ingroup/outgroup differentiation and increase the perceived overlap between the ingroup and outgroup"s characteristics. Crisp and Beck (2005) developed a task influenced by this basic idea. They found that simply asking participants to list characteristics shared between the ingroup and outgroup could reduce intergroup bias.…”
Section: Methodsmentioning
confidence: 99%
“…Categorization models of bias-reduction are linked by the general notion that they reduce ingroup/outgroup differentiation and increase the perceived overlap between the ingroup and outgroup"s characteristics. Crisp and Beck (2005) developed a task influenced by this basic idea. They found that simply asking participants to list characteristics shared between the ingroup and outgroup could reduce intergroup bias.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Crisp et al (2006) directly compared this manipulation with a simpler version (a single superordinate category label) and found both to have identical effects on evaluations as a function of identifi cation. Similarly, Crisp & Beck (2005) have shown that simple manipulations of similarity (e.g. listing fi ve characteristics that the ingroup and outgroup have in common) also exert the same effects on evaluations as a function of identifi cation as do manipulations that employ the more elaborate method used here.…”
Section: Studymentioning
confidence: 99%
“…Spears et al, 1997). Thus, perceived threat to the continuation of the initial ingroup identity via recategorization would lead to, at best, no effect on bias, or, at worst, an increase in intergroup bias (Crisp & Beck, 2005;Crisp et al, 2006;Hornsey & Hogg, 2000a;Roccas & Schwartz, 1993;van Leeuwen et al, 2003). One could argue that recategorization contexts represent little more than alternative means of manipulating intergroup similarity, something that has been examined in the social identity literature with respect to subgroup identifi cation for some time.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Asking participants to list characteristics shared between the ingroup and outgroup could reduce intergroup bias (Crisp & Beck, 2005), creating a category overlap that can reduce the salience of stereotype threat (Rosenthal & Crisp, 2006). Conversely, performance boost and selfconfidence can occur when individuals are provided with explicit downward social comparison with a devalued outgroup (Chalabaev, Stone, Sarrazin, & Croizet, 2008).…”
Section: Coping Mechanisms For Mitigating Stereotype Threatmentioning
confidence: 99%